Recompartilhamento de imagens e performance em sites de redes sociais: percepções sociossemióticas sobre a apresentação de si no facebook. - Soares, Luciano de Sampaio (2015)
Image sharing in Social Network Sites is one of the most common content publiching practices within such platforms. This action can be divided in two different procedures: iun one of them, the image is created by the user himself, while the other consists in the redistribution of content created and initially published by a third party. Basing itself in sociosemiotics (LANDOWSKI, 1992, 2002), this study aims to better understand this appropriation of imagery in order to realize how – and to which extent – reshared images can be caracterized as components of performance (GOFFMAN, 1959), the presentation an individual shows of himself during interaction, in online social network platforms, adapting such concept to a multicontextual environment, such as the one found on Facebook, by the use of dramauthenticity (WITTKOWER, 2014). To this end a universe of fanpages with relevant amounts of followers was selected, provided that their postings consisted strongly of imagery. After compiling the collected posts by type – image, status updates, or links to other websites – two sets of images, with the highest and the lowest share counts, were analyzed using Network Analysis techniques so that a qualitative angle could offer a more significant interpretation of these contents in regard to presentation of self, since they manifest themselves as syncretic and multimodal discourses by frequently allying verbal texts and imagery. From this point, this investigation aims to gather information regarding resharing practices through a parallell semi-structured questionnaire presented to Facebook users. From their responses, the ways through which the act of resharing content communicates characteristics that the individual considers pertinent to theit perceived identity are analyzed, and the body of images selected earlier – brought back in specific questions in the instrument – helps to understand how the imagery and it’s perceived characteristics become entangled in the context of presentation of self within online sociability platforns. This dissertation embeds itself primarily within the spheres of interaction and visibility regimes’s studies, as well as research regarding image, forms of seeing, and computer mediated sociability. Finally, this study also acquired a measure of understanding regarding participating Facebook users’s relation with the imagery investigated, allowing for an extrapolation os roles performed by them, considering the semiotic approach favored throughout the research, within the multiple contexts of the Facebook timeline; amd how their opinions kept or changed according to their position as sender or recipient of the resharing of the content.